Transformasi Sistem Pendidikan Islam Melalui Integrasi Teknologi Pembelajaran Digital Berbasis Model ADDIE - Sintya Ramadayani; Nazwa Maudina; Ahmad Zaki (Jurnal Keluarga Sehat Sejahtera, 2026)
The rapid development of digital technology has brought significant changes to the education sector, including Islamic education. Islamic educational institutions are required to adapt to technological advancements in order to create learning processes that are more effective, interactive, and relevant to the needs of the digital generation while maintaining Islamic values. This study aims to analyze the importance of transforming Islamic education systems through digital learning technologies, identify challenges in their implementation, and develop an innovative digital learning model based on Islamic educational principles. The study employs the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The findings indicate that the integration of digital technologies such as e-learning platforms, interactive multimedia, digital modules, educational applications, and online learning media can enhance learning effectiveness, student engagement, digital literacy, and learning motivation. Furthermore, the integration of Islamic values within digital learning contributes to the development of students’ character, morality, and ethical digital behavior. Therefore, the transformation and innovation of Islamic education through digital learning technology can serve as a strategic solution for improving the quality of Islamic education in the digital era.